Medications and Orthostatic Hypotension. Are They Complimentary or Contradictory? - Kartheek, B.R. (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTOrthostatic hypotension - a sudden fall in blood pressure when a person stands up - is a common problem in elderly adults as well as in people with multiple system atrophy, Parkinson's disease, diabetes, and a mixture of other disorders. Orthostatic hypotension is caused by loss of function in the autonomic nervous system, which controls the tightening and relaxing of blood vessels needed to maintain normal blood pressure. People with orthostatic hypotension usually experience dizziness, blurred vision, light headedness or fainting when they stand. Midodrine is the standard treatment for postural hypotension, which helps to alleviate symptoms. However, standard doses of midodrine also raise blood pressure on lying down. The treatment for postural hypotension mainly depends on the underlying cause. Mild orthostatic hypotension can be controlled by sitting or lying down immediately after feeling lightheaded upon standing. When low blood pressure is caused by medications, changing the dose of the medication or stopping it entirely controls the situation. The aim of this review is to provide comprehensive information on action of various drugs on orthostatic hypotension especially in elderly people, various associated conditions and future research opportunities. All the relevant information on orthostatic hypotension was collected through MEDLINE/PUBMED. Key words: Orthostatic hypotension, Midodrine, Blood pressure, Medication, drugs, treatment, elderly.